Challenges in circulating tumour cell research - Alix-Panabières, Catherine; Pantel, Klaus (Nature reviews. Cancer, 2014)
Circulating tumour cells (CTCs) are the subject of many published papers, but the diversity of assays used for their analysis can be daunting. This Opinion article discusses issues regarding the detection and characterization of CTCs, and poses the major outstanding questions in this field. During the past ten years, circulating tumour cells (CTCs) have received enormous attention as new biomarkers and the subject of basic research. Although CTCs are already used in numerous clinical trials, their clinical utility is still under investigation. Many issues regarding the detection and characterization of CTCs remain unknown. In this Opinion article, we propose a conceptual framework of CTC assays and point out current challenges of CTC research, which might structure this dynamic field of translational cancer research.